A STUDY OF STUDENTS’ ERRORS IN USING WRITTEN PASSIVE SENTENCE - Achmad Anang Darmawan Darmawan (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2018)
The aim of this research is to invesitgate students’ error in using English written passive sentence. The subjetcs of this research were ten second semester students of English department setudents of STKIP Al Hikmah Surabaya who took Basic English Grammar course. The objectives of this course were the students had ability in using accurate English grammar either in spoken and written for formal (scientifict and academic) or informal (daily communication) context. Passive sentence was one of grammar materials taught in this course. The objective of the material was the students were able to use passive sentence in spoken and written context. The research used descriptive quantitaive method as design of this research. The instrument of this research were documentation. The data of this research were students’ work in writing sentence using accurate passive sentence. The result of this research showed many students made errors in composing passive sentence. There were 80 errors found from students’ sentences. 45% errors made by the students when they could not use correct past participle on their sentence. The result also showed that 22,5% error found from students’ work when they omitted be as the main component of passive sentence. There were also 17,5% errors found from students sentence in using correct be form on their sentence. 15% errors were also found based on the use of accurate singular and plural component of passive sentence.